Progression of changes in left ventricular function during four days of simulated multi-stage cycling - Oosthuyse, T.; Avidon, I.; Likuwa, I.; Woodiwiss, A. J. (European Journal of Applied Physiology, 2012)
This study investigated the effect of multi-stage cycling on left ventricular function with optimal carbohydrate and fluid replacement. Eleven well-trained cyclists completed 4 days of 3 h race-simulated cycling at an average intensity of 51.8 ± 2.8 %W max with carbohydrate supplements (50 g/h). Left ventricular function was assessed by conventional echocardiography and tissue-Doppler imaging before and immediately after exercise on each day and a final recovery measurement on day 5. The rate of passive ventricular filling was persistently suppressed during repeated days of strenuous cycling (change in Septal E' wave pre to post-exercise: -3.9 ± 3.2; -1.0 ± 1.7; -1.9 ± 2.1; -2.2 ± 2.4 cm/s for day 1-4, respectively) and was not completely restored before the subsequent exercise bout. Ejection fraction was significantly reduced post-exercise on day 1 and 2 (by -6.3 ± 7.1 and -6.8 ± 7.6%, respectively), whereas the change was not significant on day 3 and 4 (-3.8 ± 8.5 and -5.5 ± 10.6%, respectively), and may be partly due to the augmented rate of late diastolic filling (Septal A' wave) noted only on day 3 and 4. Finally, resting end-diastolic volume on day 5 (recovery day) was increased compared to day 1 before exercise (127 ± 23 and 108 ± 25 ml, respectively) and may indicate secondary hypervolemia; induced to further compensate for the cardiovascular strain of multi-day exercise. Strenuous prolonged cycling even with carbohydrate replacement is sufficiently stressful to impair cardiac function. As a multi-day cycling event progresses, cardiovascular strain is mitigated by adaptations that assist in restoring systolic function, while diastolic function remains impaired.